A review of obstetric intraoperative blood cell salvage in a tertiary maternity unit. (18th April 2012) - Collins, KJ; Gardner, I; Overton, TG
Abstract : Background: Intraoperative Cell Salvage (ICS) is a well-established technique for replacing blood in other surgical specialities, but its introduction into obstetrics has been slower due to theoretical safety concerns about amniotic fluid embolism (AFE) and future haemolytic disease. Aims & Objectives: This study reviewed all cases of obstetric ICS over 2 years at a tertiary unit, to identify the proportion of patients receiving salvaged blood and any complications encountered. Methodology: 44 cases were identified through proformas completed contemporaneously by anaesthetists. Additional casenote analysis was performed. Results: The indications for ICS included placenta praevia (66%), Jehovah's witness (9%), postpartum haemorrhage (PPH – 4%), and unusual maternal antibodies (7%). 70% and 25% cases were for elective and emergency Casearean sections respectively, and 5% for laparotomies for PPH. Despite NICE recommendations, no written patient information about ICS was provided. 36% were transfused with salvaged blood. Of these, 63% of these received over 250mls blood, 1 patient received 2.2 litres, and 56% did not require additional transfusion. The proportion of salvaged blood transfused (compared to total loss) ranged from 0 to 35%. There were no cases of AFE, and there were no significant feto-maternal haemorrhages in Rhesus negative women that required additional Anti-D immunoglobulin. Few technical problems were encountered. Discussion: Our study confirms previous findings that ICS is a safe technique in obstetrics. We have produced an information leaflet to improve patient understanding. There is potential to widen ICS implementation to minimise the hazards and costs of donated blood transfusion.